Manufacturing Cycle Time Determination for a Multi-Stage Economic Production Quantity Model - Szendrovits, Andrew Z. (Management Science, 1975)
This paper presents a model which treats the manufacturing cycle time as a function of the lot size in a multi-stage production system. Using this functional relationship to determine the magnitude of the work-in-process inventory, a model is developed to calculate the economic production quantity (EPQ). The model assumes that a uniform lot size is manufactured through several operations, with only one set-up at each stage, and that transportation of sub-batches allows an overlap between operations to reduce the manufacturing cycle time. Constant fixed costs per lot, linear inventory holding costs and a constant and continuous demand of finished products are assumed over an infinite horizon. The lot size is considered “economic” when the sum of the fixed costs per lot and the inventory holding costs of both the work-in-process and finished product inventories is minimized. The model is a valid alternative to the conventional production lot size (ELQ) model which only accounts for the finished product inventory. A cost sensitivity analysis reveals the large potential savings from using the suggested EPQ model instead of the conventional ELQ model in multi-stage production systems.